(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2020)
The aim of this study is to show the Algerian National Movement’s position towards the Palestinian Issue in a specific period, i.e. 1948, and to show that the fall of Algeria under French occupation has not distracted Algeria’s attention from the Arab issues, particularly the Palestinian Cause. The study is also an attempt to show the Algerians attitude to the Palestinian cause, for this is a critical cause which is of great concern, not only to the Palestinians but to the whole Arab region. This attitude shows the political awareness of early risks arising from the establishment of a Jewish national home in Palestine. This study showed that the Algerian interest towards the Palestinian issue was not only religious due to the sanctity of the place, but it was a blend where Arabism and Islam become mingled. This study will show that the position of the Algerian nationalist movements towards the Palestinian cause, has deepened Algeria’s correlation with the Arab East issues, despite the attempts of colonialism in all its forms for the fragmentation of the Arab region, and for the occupancy of each country with its internal crises, and not outside its borders.